POTENSI ANTIMIKROBA CENGKEH : REVIEW LITERATUR - Kalalo, Marko Jeremia; Gratia, Berta; Bidulang, Crunny Bidhya; Djafar, Fadillah; Edy, Hosea Jaya (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2020)
ABSTRACT Popularity of bioactive compounds from plants as a treatment for microbial infections have increased. The content of chemical compounds in cloves can produce various biological activities. The chemical compounds contained in cloves are phenol, flavonoid, hydroxybenzoate, and hydrokinetic acid, with the main chemical compound being eugenol. This review was prepared using secondary data from the scientific literature databases of Google Scholar, PubMed, and CORE. This review aims to collect, compile, study, and highlight the potential of cloves as an antimicrobial agent from existing literature and databases. The effectiveness of cloves in treating microorganisms has a broad spectrum, including bacteria, fungi, protozoa, and viruses. The antimicrobial activity of ethanol, methanol, acetone extract, and clove essential oil provided antimicrobial activity against Gram-positive and Gram-negative bacteria. Cloves show bacteriostatic and bacteriocidic activity with mechanism of action in disrupting or damaging cell wall. Keywords : antimicrobial, clove.   ABSTRAKPopularitas senyawa bioaktif tanaman sebagai penanganan infeksi mikroba kian meningkat. Kandungan senyawa kimia cengkeh dapat menghasilkan berbagai aktivitas biologi. Senyawa kimia yang terkandung dalam cengkeh adalah fenol, flavonoid, hidroksi benzoat, dan asam hidrokinetik, dengan kandungan senyawa kimia utama eugenol. Review ini dibuat menggunakan data sekunder dari database literatur ilmiah Google Scholar, PubMed, dan CORE. Review ini bertujuan untuk mengumpulkan, menyusun, mengkaji, dan menyorot potensi cengkeh sebagai agen antimikroba dari literatur dan database yang ada. Efektivitas cengkeh dalam menghabat mikroorganisme memiliki spektrum yang luas mencakup bakteri, jamur, protozoa, dan virus. Aktivitas antimikroba ekstrak etanol, metanol, aseton, minyak atsiri cengkeh memberikan aktivitas antimikroba pada bakteri Gram positif dan Gram negatif. Cengkeh menunjukkan aktivitas bakteriostatik dan bakteriosidik dengan mekanisme merusak dinding sel. Kata kunci : antimikroba, cengkeh